Among antithrombotic agents, prasugrel, but not ticagrelor, is associated with reduced 30 day mortality in patients with ST-elevated myocardial infarction. (15th September 2015) - Serebruany, Victor L.; Cherepanov, Vasily; Tomek, Ales; Kim, Moo Hyun
Abstract: Background: ST-elevated myocardial infarction (STEMI) holds the highest early mortality among patients with acute coronary syndromes. Despite numerous claims of clinical benefits and superiority over clopidogrel, there are no head-to-head outcome randomized clinical trials (RCTs) directly comparing novel antithrombotic agents in STEMI. Moreover, since most regulatory approvals are based on a single RCT's results, their meta-analyses are rare to compare death rates. We analyzed the 30-day mortality in STEMI patients who underwent percutaneous coronary intervention (PCI) and were treated with antithrombotic agents compared to clopidogrel as a reference. Methods and results: Altogether, 10 RCT's and 1 retrospective study with a total number of 26, 658 STEMI patients were included. Random-effects model with Mantel–Heanszel weighting was used to pool outcomes into a meta-analysis. Therapy with clopidogrel was associated with 2.76% 30-day STEMI mortality which was similar to that of ticagrelor (2.6%; OR = 0.9395 [CI = 0.76 to 1.17; p = 0.58]), and for bivalirudin (2.8%; OR = 1.02 [CI = 0.82 to 1.27; p = 0.86]), but was slightly higher for heparin (3.0%; OR = 1.08 [CI = 0.86 to 1.35; p = 0.52]). There was a trend towards lower mortality after tirofiban (2.1%; OR = 0.77 [CI = 0.52 to 1.13; p = 0.20]), and cangrelor (1.7%; OR = 0.59 [CI = 0.29 to 1.20; p = 0.19]), although the sample size for both agents was woefully small. The only agent which offers a significant 30-day mortality benefit in STEMI was prasugrel with significant lowest 1.75% death rate (OR = 0.63 [CI = 0.46 to 0.86; p = 0.03]). Conclusions: Among antithrombotic agents, prasugrel, but not ticagrelor, offers significant 30-day mortality benefit over clopidogrel in PCI-treated STEMI patients justifying short-term use in such a high-risk population.